2020
DOI: 10.5395/rde.2020.45.e35
|View full text |Cite
|
Sign up to set email alerts
|

Calcium silicate-based root canal sealers: a literature review

Abstract: Epoxy resin-based sealers are currently widely used, and several studies have considered AH Plus to be the gold-standard sealer. However, it still has limitations, including possible mutagenicity, cytotoxicity, inflammatory response, and hydrophobicity. Drawing upon the advantages of mineral trioxide aggregate, calcium silicate-based sealers were introduced with high levels of biocompatibility and hydrophilicity. Because of the hydrophilic environment in root canals, water resorption and solubility of root can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 102 publications
(163 reference statements)
1
41
0
4
Order By: Relevance
“…Many formulations are available on the market. Unlike conventional root canal sealers, CSBS are hydraulic and hygroscopic with a particular setting process [ 6 ]. CSBS exhibit several interesting properties, especially biocompatibility, antimicrobial properties, and bioactivity [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many formulations are available on the market. Unlike conventional root canal sealers, CSBS are hydraulic and hygroscopic with a particular setting process [ 6 ]. CSBS exhibit several interesting properties, especially biocompatibility, antimicrobial properties, and bioactivity [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A strong and long-lasting link between the root canal wall and the filling is one aspect of the prevention of root canal infection, caused either by regrowth of microorganisms or newly gained infection due to coronal or apical leakage [32]. Endodontic sealers are used to seal minor discrepancies between the dentinal wall of the root canal and the root filling material, including irregularities in the apical foramen and canal [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the physical properties of calcium silicate-based sealers meet the recommendations of the International Organization for Standardization and have consistently been reported to be biocompatible, they have not overcome conventional resin-based sealers in actual practice [33]. The bioactivity of calcium silicate sealers depends on their solubility, even after setting, and this solubility might affect the quality of root canal sealing [26] despite bioceramic materials having been reported to have good stability over time [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, slight moisture in root canal dentin may be advantageous to sealing, but resin-based sealer is affected by it [ 3 ]. Furthermore, several studies showed that MTA-based sealers have higher biocompatibility compared to resin-based sealers [ 4 , 5 , 6 ]. However, it is generally known that MTA has limited antimicrobial effects against some microorganisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%